Experimental study of low cycling fatigue in armed concrete elements due to flexion (Gaceta Técnica, 2018)
In this work, an experimental study of low cycling fatigue in reinforced concrete elements with dominant flexural behavior is developed. The reinforced concrete elements are subjected to cycles of displacement until rupture. A total of two bending beams were tested. In each cycle, the degradation of the resistance and rigidity due to the effect of low cycling fatigue is evaluated. Preliminary results and observations are presented and discussed. The tests are relevant to develop an analytical model of non-linear behavior that describes the degradation of strength and rigidity of reinforced concrete structures subjected to severe earthquakes
Keywords: lender elements; bending failure; low cycling fatigue; reinforced concrete elements; crack propagation